Penambahan Plank Exercise Pada Latihan Hexagon Drill Terhadap Peningkatan Daya Ledak Otot Tungkai Pada Pemain Voli - Zaudyasari, Bintari; , Arif Pristianto, SSt.FT.,M.Fis (2017)
Background: The increase in leg muscle explosive power needed for a volleyball player. Exercise increases leg muscle explosive power that will be required each player to perform the technique smash and jump serve in volleyball game. One exercise that can increase the explosive power of muscles is to exercise hexagon drill and Plank exercise to increase muscle strength postural body. Physiotherapy plays an important role to provide direction, feedback, provision of training programs, rehabilitative during a sports injury. Objective: To determine whether there are differences between the groups were given or not given the addition plank exercise on a hexagon drill exercises to increase leg muscle explosive power in volleyball players. Methods: This study used an experimental method with the method pre and post treatment group design with two types of exercises are exercises Hexagon drill and additions plank exercise on exercise drill hexagon. Results: Data obtained normal distribution, the influence of different test using independent sample t-test t value diperleh 0001 -4135 significance, because sig. ˂0.05, it can be concluded there is a difference between the effects of exercise and the addition of Hexagon drill plank exercise to exercise hexagon drill to increased leg muscle explosive power in volleyball players. Conclusion: There is a hexagon drill exercise influence and plank exercise to boost leg muscle explosive power. Keywords: Volleyball, Exercise Hexagon drill, and plank exercise.